Edukasi Pencegahan Stunting melalui Kelas Interaktif Pada Santriwati Pondok Sabilul Hasanah Banyuasin - Ningsih, Windi Indah Fajar; Ramdika, Sari Bema; Mukti, Retno Cahaya (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Santriwati (female Islamic boarding school student) are within the target age range for the 8000 HPK program, making it crucial to have sufficient protein intake to prevent stunting in future generations. Fish, being a good source of protein, is widely available in Islamic boarding schools due to its nutritional value and affordable price. However, protein intake among female students in these institutions often falls into the deficit category, primarily due to a lack of knowledge about the importance of fish as a protein source. This Community Service activity aims to enhance the knowledge of female students regarding nutrition and the role of protein through interactive classes. The interactive class includes nutrition presentation, games and coloring goodie bags with the slogan